Circulating levels of hydrogen sulphide negatively correlate to nitrite levels in gestational hypertensive and preeclamptic pregnant women - Possomato-Vieira, Jose Sergio [UNESP]; Palei, Ana Carolina; Pinto-Souza, Caroline Cristina [UNESP]; Cavalli, Ricardo; Dias-Junior, Carlos Alan [UNESP]; Sandrim, Valeria [UNESP] (Wiley, 2021)
Endothelial dysfunction is a hallmark of preeclampsia and the role of nitric oxide (NO) has been extensively studied in this pregnancy complication. In recent years, hydrogen sulphide (H2S) has arisen as a new gasotransmitter with an impact on endothelial function. However, the involvement of H2S in the pathophysiology of preeclampsia is not fully understood, and only a few studies with limited sample size have investigated circulating levels of H2S in preeclamptic patients. Moreover, H2S levels have not been previously evaluated in gestational hypertension. Furthermore, the relationship between H2S and NO in these hypertensive disorders of pregnancy has yet to be determined. We measured H2S levels in plasma of 120 healthy pregnant women, 88 gestational hypertensive and 62 preeclamptic women. We also measured plasma nitrite in a subset of patients and carried out correlation analysis between plasma H2S and nitrite in these three groups. We found that plasma H2S was elevated in preeclampsia and further increased in gestational hypertension compared to healthy pregnancy. Plasma nitrite was reduced in gestational hypertension and preeclampsia, and these levels were negatively correlated with H2S in both gestational hypertension and preeclampsia, but not in healthy pregnancy. Our results indicate that increases in H2S may represent a mechanism triggered as an attempt to compensate reduced NO in gestational hypertension and preeclampsia. Future studies are warranted to investigate the mechanisms underlying H2S/NO interaction on mediating endothelial dysfunction in these hypertensive disorders of pregnancy.
Keywords: gestational hypertension; hydrogen sulphide; nitrite; preeclampsia; pregnancy